Between Water and Land: An Urban and Architectural Response to Climate Change in Red Hook, Brooklyn - Joel Towers; Martina Kohler; David Maria D’Olimpio; Cody Burchfield (Architecture, 2025)
Climate change places urban coastlines at significant risk from rising sea levels and increasing storm intensity and frequency. This paper uses Red Hook, Brooklyn, NY as a case study to identify knowledge gaps in current climate resilience efforts across low-lying, post-industrial landscapes in coastal cities. Through an analysis of the short- and long-term effects of Superstorm Sandy (29 October 2012), current city planning efforts, and resulting architectural adaptations, this paper uncovers the shortcomings and possible maladaptive planning in Red Hook and New York City’s overall coastal resilience efforts. As a response to these findings, a new framing for future resilience efforts is proposed through speculative student design proposals and international case studies, applying a more dynamic understanding of climate resilience. These proposals envision a future climate-resilient, heterogeneous model for post-industrial coastal neighborhoods, transitioning to urban landscapes that embrace their shifting shorelines. This paper’s conclusion argues that effective coastal resilience requires strategies that work at multiple scales with shifting water–land boundaries rather than against them.